Lipovetsky e a hipermodernidade: dilemas e perspectivas para a moderna noção de sujeito e a ética - Cruz, Daniel Nery da (Universidade do Vale do Rio dos Sinos, 2013)
Giles Lipovestky's arguments about the contemporary era and its implications, extended to an analysis on moral issues, are the main approaches of this work. We live in a context where the roots of postmodern moral problems are fragmentary. Assuming an optimistic stance on this new scenario, Lipovetksy in turn presents the ethics of post-duty, an approach criticized by Bauman. This dissertation presents a comparison between these two positions, indicating possible similarities and contrasts between them.
Keywords: Lipovetsky; Hipermodernidade; Pós-modernidade; Hypermodern; Postmodernity; ACCNPQ::Ciências Humanas::Filosofia